Combined use of recycled powder and recycled coarse aggregate derived from construction and demolition waste in self-compacting concrete. (10th September 2020) - Duan, Zhenhua; Singh, Amardeep; Xiao, Jianzhuang; Hou, Shaodan
Highlights: Hardened properties of self-compacting recycled concrete (SCRC) were analyzed. Self-compacting characteristics were maintained when RCA and RP were used. The use of FA, SF and RP in SCC mixtures can improve the durability properties. Increasing RP content leads to a significant increase in the total porosity. RCA and RP have potential to be used as raw material in developing Eco-friendly SCC. Abstract: This study aims to investigate the properties of self-compacting concrete (SCC) with a combined use of recycled coarse aggregate (RCA-0, 25%, 50% and 100% replacement by mass) and recycled powder (RP-10% and 20%), which were both derived from construction and demolition (C&D) waste. Fresh properties were conducted as per EFNARC and porosity was evaluated by using a non-destructive test technique micro X-ray Computer Tomography (X-ray CT). The results showed that SCC mixtures examined in this study all owed excellent flow-ability even when FA was fully replaced with RP. The compressive strength, splitting tensile strength and the resistance to chloride penetration of SCC generally weakened with an increase in the RCA replacement, and the rate of reduction was generally lower when RCA was used no more than 50%. X-ray CT results showed that a higher amount of RP can lead to agglomeration of particles that lead to higher porosity in concrete, which may attribute to the poor durability of SCC with RCA and RP.